Applying Person‐Environment Fit Theory to Identify Personality Differences between Prospective Social and Commercial Entrepreneurs: An Explorative Study. (1st July 2019) - Riedo, Valerie; Kraiczy, Nils Daniel; Hack, Andreas
Abstract : Research has started to investigate personality traits of social entrepreneurs because such traits in commercial entrepreneurs have been found to affect new venture creation/success. In this exploratory study, we apply the person‐environment fit theory and analyze specific social entrepreneurial personality dimensions (i.e., altruism, empathic concern, personal distress, compassion), and classical entrepreneurial personality dimensions (i.e., need for achievement (nAch), entrepreneurial self‐efficacy (ESE), general self‐efficacy, risk‐taking propensity) to identify differences between prospective social and commercial entrepreneurs. Using a sample of 85 prospective entrepreneurs, results show that prospective social entrepreneurs differ from prospective commercial entrepreneurs in the personality dimensions of personal distress, nAch, ESE, and risk‐taking propensity.